Apomediation, AI, and the illusion of autonomy: risks of misinformation in patient decision-making - Ponce-Rojo, Antonio; Fontaines-Ruiz, Tomás; Romero-Rodríguez, Luis M. (Frontiers in Communication, 2026)
The increasing integration of generative artificial intelligence (AI) in digital health is transforming apomediation into AIMediation, which reconfigures patient autonomy and raises ethical concerns that must be addressed. This study examines how algorithmic curation, personalized interfaces, and conversational agents redefine what information becomes visible and trustworthy, generating an illusion of autonomy that can mask the erosion of real decision-making capacity. Based on an exploratory synthesis of the recent literature (n = 38), three dimensions are analyzed: algorithmic intermediation, perceived autonomy, and informational vulnerability, with attention to cognitive overload and the amplification of biases in seeking health information. Evidence indicates that AIMediation can improve access to and understanding of health information but also intensify risks, such as misinformation and reliance on opaque outcomes, posing challenges to safeguarding transparency, patient agency, and equitable access to reliable information.